A new 5-input majority gate without adjacent inputs crosstalk effect in QCA technology - Ali Majeed; Esam Alkaldy; Mohd Shamian Zainal; Danial Md Nor (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Transistor-based CMOS technology has many drawbacks such as power consumption and cannot continue in following the scaling of Moore's law and system-on-a-chip in near future. These drawbacks lead the researchers to think about an alternative technology. Quantum-dot Cellular Automata (QCA) is a new nanoscale technology can implement the logical functionality by controlling the position of the electron. The basic building blocks for QCA circuit are majority gate and inverter. where AND and OR gate can be implemented using Majority gate by setting one of the inputs to "0" and "1" respectively. A lot of papers was introduced to propose a new gates construction such as XOR and 5- input majority gate in last few years. The complexity of the gate leads to the complexity of the whole circuit so whenever the proposed gate has a lower number of cells, that's mean it’s better. In this paper, we introduce a new construction of a novel 5- input majority gate. QCADesigner tool will be used to show the simulation result of the proposed gate. Then we will compare the proposed gate with the most important previous counterpart gates.